Causes of variation orders in the Egyptian construction industry: Classification, ranking, and mitigation - El-Sadek, Amr Khaled (AUC Knowledge Fountain, 2015)
Variations or change orders are inevitable in any construction project. They are defined as any change that happens in the scope of the project whether this change is an additional scope of work, omission, or even alteration. This thesis presents the causes of variation orders in Egypt. The literature review divides the causes into four main categories: owner related, contractor related, consultant related, and other causes. All the identified events were surveyed in a questionnaire given to top executives in the construction field in Egypt. The survey was distributed equally on clients, consultants, and contractors. The top 10 most important causes are ranked among the opinion of each party. Another list of the least 10 important causes of variation orders is presented as well. It was found out that when adding up all the results, the most important cause of variations is that the client instructs additional work, followed by contractor using grey areas in the contract to request variations, and continuous changes in schedule. A comparison was done between Egypt, Palestine, Malaysia, and the United Kingdom. It was found it that problems related to design are mentioned directly or indirectly in every country, but there is no overall similarity when comparing all the countries against each other. Further to data analysis, a model was created using the collected data base. This model provides the user with a scale that predicts the effect of the events triggering variations on both project cost and time. The model was validated using a case study about a large retail shopping center that was recently completed and has proven to be helpful. Finally, the research also provides a list of mitigation techniques that can help reduce the events that give rise to variations. The list of recommendation was validated through a survey given to professionals in the industry to insure their authenticity for the thesis.